Towards a Catalog of Heuristics for the Design of Systems-of-Systems - Imamura, Marcio; Ferreira, Francisco; Fernandes, Juliana; Graciano Neto, Valdemar Vicente; Santos, Rodrigo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
Context: Systems-of-Systems (SoS) are arrangements of independent systems that are increasingly present in everyday life and can be observed in domains such as healthcare, transport, and Industry 4.0, to mention a few. Problem: A significant concern regarding SoS refers to the constituent systems’ (CS) independence. CS are managed by different organizations that control them independently of SoS. Hence, the design of SoS is challenging as it involves careful investigation, allocation, and integration of CS to ensure proper operation. Solution: This paper provides a catalog of good practices and recommendations, herein referred to as “heuristics”, which can be applied to the SoS design. The main purpose of the catalog is to provide directions on what practitioners should consider during the design phase to ensure the proper operation of the SoS. IS theory: This research is based on the General Systems Theory that allows understanding SoS as a complex system constructed with independent systems. Method: We conducted a systematic mapping study (SMS) to identify which heuristics have been applied to SoS design. The results were discussed in a focus group with professionals to organize the heuristics. Summary of Results: After reaching a consensus on the focus group, we organized a catalog of fifteen heuristics into five categories: initiation, CS, interoperability, emergent behavior, and monitoring. Contributions and Impact in the IS area: The heuristics catalog, which is grounded in the literature, would support researchers and professionals in identifying critical issues during the SoS design phase.